2007
DOI: 10.1111/j.1471-4159.2007.04743.x
|View full text |Cite
|
Sign up to set email alerts
|

Leucine‐rich repeat kinase 2 (LRRK2)/PARK8 possesses GTPase activity that is altered in familial Parkinson’s disease R1441C/G mutants

Abstract: Mutations in Leucine-rich repeat kinase 2 (LRRK2) are linked to the most common familial forms and some sporadic forms of Parkinson's disease (PD). The LRRK2 protein contains two well-known functional domains, MAPKKK-like kinase and Rab-like GTPase domains. Emerging evidence shows that LRRK2 contains kinase activity which is enhanced in several PD-associated mutants of LRRK2. However, the GTPase activity of LRRK2 has yet to be formally demonstrated. Here, we produced and purified the epitope-tagged LRRK2 prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
254
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(276 citation statements)
references
References 24 publications
21
254
1
Order By: Relevance
“…In humans, however, it is unknown whether loss-of-function mutations in LRRK2 lead to dopaminergic cell death. On the contrary, it seems that it is increased/constitutive activity of the LRRK2 protein (West et al 2005;Gloeckner et al 2006;Smith et al 2006;Guo et al 2007;Li et al 2007). In summary, researchers in this field should be very careful before extrapolating results obtained for protostome LRRK genes to humans.…”
Section: Discussionmentioning
confidence: 98%
“…In humans, however, it is unknown whether loss-of-function mutations in LRRK2 lead to dopaminergic cell death. On the contrary, it seems that it is increased/constitutive activity of the LRRK2 protein (West et al 2005;Gloeckner et al 2006;Smith et al 2006;Guo et al 2007;Li et al 2007). In summary, researchers in this field should be very careful before extrapolating results obtained for protostome LRRK genes to humans.…”
Section: Discussionmentioning
confidence: 98%
“…The GTPase activity for N1437H has not been determined, but it has been shown that this mutant has increased GTP binding [13], which is consistent with lower GTPase activity. The reported GTP-binding capacity of R1441C/G and Y1699C is less consistent, with some reports of an increase and others finding no change in GTP binding [45,47,48]. These effects are probably related, as it has been proposed that the ROC and COR domains may interact with each other.…”
Section: Pathogenic Mutations In Pd Affect Protein Functionmentioning
confidence: 95%
“…In mice, during embryonic development LRRK2 mRNA expression is not detectable before E15 after which it steadily rises, suggesting it is not an essential developmental gene [31]. Lrrk2 protein is evident by E17 [31] and continues to rise progressively and peaks around P60 [33]. Levels of Lrrk2 remain constant in rodents during aging [34].…”
Section: Anatomical Localization Of Lrrk2mentioning
confidence: 99%
“…Outside of the CNS, high expression is found in the lungs, kidney, spleen and leucocytes [3,[31][32][33][34]. In mice, during embryonic development LRRK2 mRNA expression is not detectable before E15 after which it steadily rises, suggesting it is not an essential developmental gene [31].…”
Section: Anatomical Localization Of Lrrk2mentioning
confidence: 99%
See 1 more Smart Citation